STUDY OF RUDDER EFFECTIVENESS DUE TO THE EFFECT OF CHINNED FOREBODY ON THE LATERAL DIRECTIONAL STABILITY OF THE XF-103 FIGHTER AIRCRAFT WITH WATER TUNNEL - Hugo Ariesta, Mal
One of the Main Defense System Equipment development projects needed to defend the sovereignty of the Republic of Indonesia is the development of the XF-103 fighter aircraft. The XF-103 fighter aircraft is designed to be able to perform a variety of maneuvers in its operations, including the ability to fly at a high angle of attack. The Chined Forebody configuration was chosen for use on the XF-103 fighter because it increases the stealth effect and also has the ability to provide additional lift at a high angle of attack so as to delay a stall. The chinned forebody configuration on the XF-103 fighter aircraft will be studied for its effect on rudder effectiveness on directional lateral stability in testing using a water tunnel. The basic chinned forebody model of the XF-103 aircraft has been tested in the BPPT-Indonesia ILST wind tunnel, but due to the relatively high cost of the test, it was tested with the water tunnel equipment available at PT. Indonesian Aerospace. The data from the basic chinned forebody model XF-103 test results from the wind tunnel are used as references to validate the water tunnel. Because the flow medium used by water tunnel is different from the wind tunnel so that the Reynolds Number is much different, the validation uses a qualitative approach. This approach is carried out because the trend of the test results data shows similarities so that the water tunnel testing can be used as material for the study. The chinned forebody configuration was varied into "Basic", "Chin1", "Chin2" and "LEX3" for comparison. Each configuration undergoes force and moment measurements for Alpha angles from -4 to +44 degrees (2 degrees increments), Beta angles of -10, 0 and +10 and rudder deflections of -20, 0 and +20 degrees. In addition to measuring forces and moments, observations were also made to visualize the flow that occurred. This study shows that the variation of chinned forebody configurations in the form of Basic, Chin1 and Chin2 has relative the same effect on rudder effectiveness and is smaller than the configuration with LEX3. This is because LEX3 is more capable of generating a vortex which maintains the quality of flow towards the rudder.